Synonymy of the reduviid (Hemiptera: Heteroptera) genus Torrealbaia (Triatominae) with Amphibolus (Harpactorinae), with notes on Amphibolus venator (Klug, 1830) - Forero, Dimitri; Weirauch, Christiane; Baena, Manuel (Zootaxa, 2004)
The monotypic reduviid genus Torrealbaia Carcavallo, Jurberg & Lent, 1998 (Triatominae, Cavernicolini) from Venezuela is synonymized with Amphibolus Klug, 1830 (Harpactorinae) described from Northern Africa. Morphological evidence for the synonymy of Torrealbaia martinezi Carcavallo, Jurberg & Lent, 1998 with Amphibolus venator (Klug, 1830) is discussed. The currently known distribution of A. venator (Northern Africa and the Middle East, Jamaica, India, Japan) is supplemented by new locality data from Venezuela, Canada and India. It is hypothesized that the distributional records of A. venator from the Neotropical region are due to dispersal of this species by human means, possibly with stored products.